Determination of The Minimal Amount of Water for Effective Suppression of The Thermal Decomposition of Forest Combustible Materials; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Zhdanova A. O. Alena Olegovna (2016, 2016)
Title screen